2018
DOI: 10.1039/c8tc00110c
|View full text |Cite
|
Sign up to set email alerts
|

Roll to roll atmospheric pressure plasma enhanced CVD of titania as a step towards the realisation of large area perovskite solar cell technology

Abstract: Highly effective TiO2−x electron transport layers produced by continuous atmospheric pressure PECVD achieve efficiency gains in mesoporous perovskite photovoltaic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Lead halide perovskite nanocrystals (LHP NCs) are being increasingly used as active materials in different optoelectronic devices such as light-emitting diodes and solar cells. Although it is possible to fabricate these devices fully by solution processes, it is also common to employ plasma-assisted processes such as plasma-enhanced chemical vapor deposition or plasma-enhanced atomic layer deposition for the formation of various layers acting as charge-extraction materials or antireflective coatings. For perovskite devices, plasma-assisted processes have been used for the deposition of bottom layers of TiO 2 and SnO 2 . Xiao et al have also demonstrated the beneficial use of argon plasma directly on perovskite films, while others have grown protective alumina layers on perovskites by atomic layer deposition .…”
mentioning
confidence: 99%
“…Lead halide perovskite nanocrystals (LHP NCs) are being increasingly used as active materials in different optoelectronic devices such as light-emitting diodes and solar cells. Although it is possible to fabricate these devices fully by solution processes, it is also common to employ plasma-assisted processes such as plasma-enhanced chemical vapor deposition or plasma-enhanced atomic layer deposition for the formation of various layers acting as charge-extraction materials or antireflective coatings. For perovskite devices, plasma-assisted processes have been used for the deposition of bottom layers of TiO 2 and SnO 2 . Xiao et al have also demonstrated the beneficial use of argon plasma directly on perovskite films, while others have grown protective alumina layers on perovskites by atomic layer deposition .…”
mentioning
confidence: 99%
“…Technically, the roll-to-roll plasma system used Argon gas flow and an audio frequency power supply (3.4 kHz) which activated the plasma under a potential of 4 and 8 kV to achieve 10.68 m hr −1 line speed for the deposition of mesoporous TiO 2 film (Hodgkinson et al, 2018). The deposited film served as the hole blocking layer coated on top of the TCO of the solar cell; afterward, the performance of the device was compared to a reference cell with the TiO 2-x electron transport layer sputtered using an RF source at 60oC in argon along with oxygen at a pressure of 7.5 x 10 −6 mbar (Hodgkinson et al, 2018). It is worth mentioning that this strategy consisting in the tuning of the electronic properties of the Electron transport layer and/or hole transport layer was found to be beneficial in the decline of their parasitic absorption (Li et al, 2020b).…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…Interestingly, several approaches were found to considerably enhance the efficiency of PV solar cells; these include intrinsic and extrinsic factors, both related to the thin films' deposition techniques (Kemell et al, 2005). Generally, thin film solar cell components are fabricated using various vacuum and non-vacuum deposition techniques such as sol-gel spin coating, spray coating, doctor blade, drop casting, dip coating, ink-jet evaporation, Pulsed Laser Deposition, Chemical Vapor Deposition (MOCVD), Molecular Beam Epitaxy (MBE), Electron-Beam Physical Vapor Deposition (EBPVD), magnetron sputtering, and Plasma Enhanced Chemical Vapor Deposition (PECVD) (Steirer et al, 2009;Eslamian, 2014;Eslamian and Zabihi, 2015;Lu et al, 2015;Leyden et al, 2016;Farrag and Balboul, 2017;Matur and Baydogan, 2017;Hodgkinson et al, 2018;Abzieher et al, 2019;Ji et al, 2019;Lim et al, 2021a;Smirnov et al, 2021;Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In order to attain higher efficiencies of the graphene-based PSCs, how to further reduce the sheet resistance of graphene films is a key problem. Im and his coworkers employed AuCl 3 -doped graphene [116,117,118] and amide TFSA-doped graphene [109] as bottom electrodes to make super-flexible PSCs. After highly p-type chemical doping with two dopants, the sheet resistance of single layer graphene film decreased significantly to approximately 100 Ω sq −1 , which is much lower than the monolayer graphene.…”
Section: Electrode Window Blocking and Electron Transport Layer mentioning
confidence: 99%
“…Large area and functional TiO 2−x films using as the hole blocking electron transport layers in PSC architectures are synthesized by roll to roll PECVD system [116]. The PECVD system has a dual laminar flow design to provide two reaction zones to improve net growth rate and uniformity and minimize the entrainment of surrounding air.…”
Section: Electrode Window Blocking and Electron Transport Layer mentioning
confidence: 99%